IOT BASED FAULT DETECTION IN TRANSMISSION LINE - Jagruti Bangal; Ajinkya Bhagat; Sanchit Bhoir; Vaishali Kende; Vishal Patil; Dr. Sharvari Sane (International Engineering Journal For Research & Development, 2023)
This study aims in energy monitoring and transmission line post fall detecting system. Protection of transmission line is important, because 85-87% faults of power system occur in these transmission lines. In this study, it presents a method and technology to detect and classify the various shunt faults on a transmission line for quicker and reliable function of protection schemes.In the Transmission Line Falling Detection System, the 3 axis position sensor will be used to detect any post fall and line fall. Microcontroller is implemented in this method and accelerometer sensor is used to detect position of transmission line stand. It also detects the line connections of the post. GSM modem is used to send data from microcontroller to Cloud with location and post number and inform the nearest power station.